MEMEs: modern evolutionary medical euphemisms. (11th December 2015) - Isaacs, David; Isaacs, Stephen; Fitzgerald, Dominic
Abstract : David Isaacs and colleagues propose the modern evolutionary medical euphemism—a way of never being totally frank if a more palatable alternative can be used